ANALISIS PENGAKUAN PENDAPATAN DAN BEBAN PT. TBK SAMARINDA BERDASARKAN PSAK NO 34 ( REVISI 2015 ) - Wulandari, - Amelia (EKONOMIA, 2019)
Revenue and Expense Recognition Analysis of PT.TBK Samarinda  Based on PSAK No. 34 (Revised 2015) period of  February 2018 under the guidance of Robin Jhonatan and Ivana Nina Esterlin Barus.This writing aims to determine the recognition of income and expenses PT. TBK Samarinda are in compliance with PSAK No. 34 (Revision 2015) or not.The author put forward the hypothesis as follows: "that the recognition of income and expenses on the company of PT. TBK  Samarinda have not complied with Statement of Financial Accounting Standards (PSAK) No. 34 (Revised 2015). "To test the truth of the hypothesis that has been proposed, the authors compare the calculation of financial statements of PT. TBK Samarinda with financial statements according to Statement of  Financial Accounting Standards (PSAK) No. 34 (Revision 2015) which the result is the calculation of PT. TBK Samarinda have not complied with Statement of Financial Accounting Standards (PSAK) No. 34 (Revised 2015).From the results of the analysis it can be concluded that the recognition of income at PT. TBK Samarinda are companies recognizing revenues based on physical progress in which the company recognizes physical based on settlement income, whereas based on PSAK No. 34 (Revised 2015) using cost to cost method, cost to cost approach method gives a more reasonable description in recognizing income when compared with physical approach so that the author's hypothesis is accepted.